Applications manual essentials of anatomy and physiology - Frederick H Martini (Prentice-Hall, 1997)
This book provides a wealth of supplemental material that can greatly enrich the study of anatomy and physiology. It allows the student to explore many applied topics in greater depth while also providing relevant background information and a valuable librry of photographic images.